Adenovirus vector-mediated single chain variable fragments target the nucleocapsid protein of porcine epidemic diarrhea virus and protect against viral infection in piglets - Wang, Fengqing; Zhang, Qing; Zhang, Fanqing; Zhang, En; Li, Mei; Ma, Shiwei; Guo, Jianming; Yang, Zhibiao; Zhu, Jianguo (Frontiers in Immunology, 2023)
Porcine epidemic diarrhea virus (PEDV) mainly infects the intestinal epithelial cells of pigs, causing porcine epidemic diarrhea (PED). In particular, the virus causes severe diarrhea, dehydration, and death in neonatal piglets. Maternal immunity effectively protects neonatal piglets from PEDV infection; however, maternal antibodies can only prevent PEDV attachment and entry into target cells, but have no effects on intracellular viruses. Intracellular antibodies targeting virus-encoded proteins are effective in preventing viral infection. We previously identified four single chain variable fragments (scFvs), ZW1-16, ZW3-21, ZW1-41, and ZW4-16, which specifically targeted the PEDV N protein and significantly inhibited PEDV replication and up-regulated interferon-λ1 (IFN-λ1) expression in host cells. In our current study, the four scFvs were subcloned into replication-defective adenovirus vectors to generate recombinant adenoviruses rAdV-ZW1-16, rAdV-ZW3-21, rAdV-ZW1-41, and rAdV-ZW4-16. ScFvs were successfully expressed in Human Embryonic Kidney 293 (HEK293) cells and intestinal porcine epithelial cell line J2 (IPEC-J2) and were biosafe for piglets as indicated by body temperature and weight, scFv excretion in feces, IFN-γ and interleukin-4 (IL-4) expression in jejunum, and pathological changes in porcine tissue after oral administration. Western blotting, immunofluorescence, and immunohistochemical analyses showed that scFvs were expressed in porcine jejunum. The prophylactic effects of rAdV-ZW, a cocktail of the four rAdV-scFvs, on piglet diarrhea caused by PEDV was investigated. Clinical symptoms in piglets orally challenged with PEDV, following a two-time treatment with rAdV-ZW, were significantly reduced when compared with PEDV-infected piglets treated with phosphate buffered saline (PBS) or rAdV-wild-type. Also, no death and jejunal lesions were observed. ScFv co-localization with the PEDV N protein in vivo was also observed. Next, the expression of pro-inflammatory serum cytokines such as tumor necrosis factor-α (TNF-α), IL-6, IL-8, IL-12, and IFN-λ was assessed by enzyme-linked immunosorbent assay (ELISA), which showed that scFvs significantly suppressed PEDV-induced pro-inflammatory cytokine expression and restored PEDV-inhibited IFN-λ expression. Therefore, our study supported a promising role for intracellular scFvs targeting the PEDV N protein to prevent and treat diarrhea in PEDV-infected piglets.